2018
DOI: 10.1177/0197918318766359
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Immigrant Status and Age at Migration on Changes in Older Europeans’ Health

Abstract: The purpose of this study was to determine the differences between natives and immigrants in regard to transition probabilities among health states in self-rated health (SRH), depression, and activities of daily living for middle-aged and older adults in Europe. The Survey of Health, Aging, and Retirement allows us to investigate how successfully the immigrants have aged from 2004 to 2011 compared to natives, according to country of origin and age at migration. We showed that some groups, such as Eastern Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…The areas of research are different and over time they gradually change in connection with changing cultural, social, economic, or political changes in society. International migration over the last half century has significantly affected individual states in Europe (Lanari, Bussini and Minelli, 2018). This is also confirmed by Triandafyllida ( 2018), who claims that migration has intensified and diversified over the last 25 years.…”
Section: Literature Reviewmentioning
confidence: 76%
“…The areas of research are different and over time they gradually change in connection with changing cultural, social, economic, or political changes in society. International migration over the last half century has significantly affected individual states in Europe (Lanari, Bussini and Minelli, 2018). This is also confirmed by Triandafyllida ( 2018), who claims that migration has intensified and diversified over the last 25 years.…”
Section: Literature Reviewmentioning
confidence: 76%
“…In contrast, a negative association was found between older age and SWL, although this association was stronger in the Latin American group. Other studies have also found an association between older age and integration problems (Genkova, Trickett, Birman, & Vinokurov, 2014; Millán‐Franco, Gómez‐Jacinto, Hombrados‐Mendieta, García‐Martín & García‐Cid, 2019) and health problems (Lanari, Bussini, & Minelli, 2018).…”
Section: Discussionmentioning
confidence: 91%
“…Positive associations between length of stay and mental health outcomes were found among immigrants in Canada (Bagley, 1993) and immigrants in Sweden (Koochek et al, 2007;Leão et al, 2009). By contrast, other studies have found negative associations between length of stay and mental health in adult immigrants living in Europe (Honkaniemi et al, 2020;Lanari & Bussini, 2012). The latter findings support the claim that a possible Healthy Migrant Effect for mental health (a mental health advantage upon arrival of immigrants in their new home countries) diminishes over time (Wu & Schimmele, 2005).…”
mentioning
confidence: 77%
“…There is differing evidence concerning possible associations between age at immigration and mental health in immigrants and their children. While some studies from North America reveal a negative impact of childhood immigration (Islam et al, 2014;Patterson et al, 2013), studies from Europe find increased odds of mental health problems in older immigrants (Honkaniemi et al, 2020;Lanari et al, 2018). A benefit of young age at immigration is often explained by a better and faster adaptation to the host country.…”
mentioning
confidence: 99%